IMPROVING THE MECHANISMS OF INDIVIDUALIZING THE EDUCATIONAL AND TRAINING PROCESS OF YOUNG NATIONAL WRESTLERS AT THE INITIAL STAGES OF TRAINING - o‘g‘li, Amirov Anvar Saidmurod (Research Focus International Scientific Journal, 2026)
This article discusses the improvement of mechanisms for individualizing the educational and training process of young national wrestlers at the initial stages of training. The study analyses effective methods of organizing training sessions by considering athletes’ age, physical fitness, psychological condition, and individual abilities. In addition, the importance of modern pedagogical technologies, differentiated approaches, and individual planning in the coach’s pedagogical activity is highlighted. As a result, methodological recommendations aimed at improving the physical development, technical-tactical skills, and moral education of young wrestlers have been developed.